Catastrophizing, Functional Disability and Pain Reports in Adults with Chronic Low Back Pain - Theresa L Vienneau; Alexander J Clark; Mary E Lynch; Michael JL Sullivan (Pain Research and Management)
OBJECTIVE: To test the hypothesis that subjective reports of pain severity, pain intensity and functional disability correlate positively with catastrophizing.